Non-extraction orthodontic treatment in management of moderately crowded class II division 2 malocclusion: a case report - Othman, S.A. (2006)
A case report of a 13-year old male presented in his mixed dentition stage with a Class II division 2 incisor relationship on a mild Class II skeletal base, complicated by an increased overbite, retroclined upper and lower incisors (bimaxillary retroclination) and moderate crowding in the upper and lower labial segments. Treatment was undertaken without extraction employing an upper removable appliance with a flat anterior bite plane to correct the overbite, and an anterior screw to proclined the upper incisors while waiting for the eruption of the permanent teeth. Pre-adjusted edgewise fixed appliances were placed in the lower arch, then in the upper arch to level and align the dentition, achieve Class I incisor relationship, reduced the interincisal angle and close residual spaces. ABSTRACT FROM AUTHOR Copyright of Malaysian Dental Journal is the property of Malaysian Dental Association and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract.